Larangan Minum Minuman Keras bagi Imam Berdasarkan Imamat 10:8-11 dan Implementasinya bagi Gembala Jemaat - Alferdi Alferdi; Yulita Arruan; Resvin Tapparan; Karisma Nari (CARAKA: Jurnal Teologi Biblika dan Praktika, 2022)
Abstract The purpose of writing this article is to provide an understanding to the church pastor about the prohibition of drinking alcohol as viewed from Leviticus 10: 8-11. Liquor (alcoholic drink) is often a matter of debate because on the other hand there are some who think that liquor is something that can increase the excitement of appearing, but if it is examined further, many negative things arise from consuming liquor. This is triggered because liquor contains alcohol which can be intoxicating. This study uses a qualitative descriptive method by analyzing the phenomena that occur, and utilizing various literatures such as books and journals. This research shows that there is a prohibition for the Imam to drink liquor because alcohol contains alcohol which can have a negative impact. In addition, as priests who are representatives of the people in offering sacrifices, they are required to be holy so they can enter the temple and can carry out their duties responsibly. To maintain this holiness in the book of Leviticus 10: 8-11 expressly prohibits priests from drinking alcoholic beverages. . Seeing this reality, if it is related to church leaders today, namely the Shepherd, it is fitting to maintain holiness, especially when leading worship. The pastor of the church is expected to be able to avoid alcoholic beverages such as those contained in the book of Leviticus.